Adecuación y Puesta En Marcha de un Automóvil Como Banco Educativo Para El Programa De Ingeniería Mecánica UAN (2016)
This project presents the restoration of a car with systems in poor condition located in the facilities of the automotive mechanics workshop of the Antonio Nariño University, Neiva headquarters, the design and manufacture of a fault module to simulate four of these in three systems. of the automotive industry, applying fields of knowledge, such as automotive mechanics, automotive electricity and electronics, and automobile mechanics.